2015
DOI: 10.5194/nhess-15-147-2015
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal responses of precipitation in the Ganges and Brahmaputra river basins to ENSO and Indian Ocean dipole modes: implications for flooding and drought

Abstract: Abstract. We evaluated the spatial and seasonal responses of precipitation in the Ganges and Brahmaputra basins as modulated by the El Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) modes using Global Precipitation Climatology Centre (GPCC) full data reanalysis of monthly global land-surface precipitation data from 1901 to 2010 with a spatial resolution of 0.5 • × 0.5 • . The GPCC monthly total precipitation climatology targeting the period 1951-2000 was used to compute gridded monthly anomalie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 44 publications
(72 reference statements)
3
35
0
Order By: Relevance
“…Figure 10e, showing the spatial distributions of SWS anomalies for July 1998, illustrates well the patterns of these major flood events with large positive anomalies over the entire GB system. On the other hand, it is interesting to note that SWS estimates in 1994, which is characterized as a drought year, are below the mean seasonal cycle only for the Brahmaputra basin as reported in [64]. Nevertheless, Figure 10d shows that major drought patterns are well observed over the Brahmaputra and the main channel of the Ganges.…”
Section: Resultsmentioning
confidence: 71%
“…Figure 10e, showing the spatial distributions of SWS anomalies for July 1998, illustrates well the patterns of these major flood events with large positive anomalies over the entire GB system. On the other hand, it is interesting to note that SWS estimates in 1994, which is characterized as a drought year, are below the mean seasonal cycle only for the Brahmaputra basin as reported in [64]. Nevertheless, Figure 10d shows that major drought patterns are well observed over the Brahmaputra and the main channel of the Ganges.…”
Section: Resultsmentioning
confidence: 71%
“…No other alternative sources of observed daily precipitation were found to fill the data gap for 2002; therefore, we omitted the year 2002 from the analysis. The spatial distribution of the observed stations, characteristics of the GSOD observed precipitation, and few related examples where GSOD data have been utilized can be found in [15,18,[32][33][34]. Study showed that precipitation in these basins were well captured in GSOD data compared to satellite-driven rainfall products [35] such as NOAA Climate Prediction Center Morphing Technique [36] and Tropical Rainfall Measuring Mission [37] data.…”
Section: Methodsmentioning
confidence: 99%
“…The well-known IO Dipole Mode Index (DMI saji ) defined by [5] characterizes the pattern of differential heating in the tropical IO and is composed of SST anomalies averaged across specific areas in the west (50 • E-70 • E, 10 • S-10 • N) and the east (90 • E-110 • E, 10 • S-Equator) [5]. It is now well known that the tropical DMI and ENSO are largely independent coupled phenomena [5] that have a strong influence on the precipitation of east Africa [8], southern Africa [9], Indonesia [10], Sri Lanka [11], Australia [12], and India [13,14] with spatial differences [15]. The influence of these climate modes is likely to persist into the future as the DMI is likely to remain active and El Niño events may likely intensify due to the warming climate, according to the Intergovernmental Panel on Climate Change's Fifth Assessment Report (AR5) on the physical basis of climate change [16].…”
Section: Introductionmentioning
confidence: 99%
“…This year was both an El Niño and a positive IOD year ( Figure 11; Table 2). Even though the effect of El Niño and positive IOD may have been expected to cancel each other out [15,25], the severe drought of 2015 might be due to the three months of the El Niño event occurring before the positive IOD mode (in 2015 NINO3 > 1 occurred three months earlier than DMI > 1; Figure 16). Soil moisture (Figure 16a) and fractional water (Figure 16b) in 2015 were well below the minimum boundary envelope of the neutral years.…”
Section: Amsr Variables Response To El Niña Southern Oscillation and mentioning
confidence: 99%